2017
DOI: 10.4103/2249-4863.220037
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-care practices and assessment of their sociodemographic risk factors among diabetes in the urban slums of Bengaluru

Abstract: Objective:The objective of this study was to determine the prevalence of self-care practices in the urban slums of Bengaluru among diabetes and also to assess their sociodemographic risk factors.Materials and Methods:A cross-sectional study was done in the two slums of Bengaluru comprising 163 diabetes patients. The prevalence of self-care practices and their sociodemographic risk was analyzed.Results:Maximum adherence was seen for blood sugar testing (77.91%), and least adherence was seen for diet (12.26%). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
14
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 11 publications
10
14
2
Order By: Relevance
“…The prevalence of good exercise behavior (30.3%) in the present study was similar to that of the study carried out in the Bengaluru slum (30.67%),[ 13 ] higher to the study conducted at Vellore (19.5%)[ 12 ] and at Kollam (24.1%),[ 14 ] but lower to the study conducted in Delhi (60.7%)[ 16 ] and at Mangalore hospital (43.4%). [ 21 ]…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The prevalence of good exercise behavior (30.3%) in the present study was similar to that of the study carried out in the Bengaluru slum (30.67%),[ 13 ] higher to the study conducted at Vellore (19.5%)[ 12 ] and at Kollam (24.1%),[ 14 ] but lower to the study conducted in Delhi (60.7%)[ 16 ] and at Mangalore hospital (43.4%). [ 21 ]…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the prevalence of good dietary behavior (29.8%) was almost similar with the study carried out in an urban community in Vellore (29%),[ 12 ] rural Karnataka (24%),[ 15 ] Delhi (31%),[ 16 ] and Chennai (37%),[ 17 ] but was higher in comparison to the study conducted in a Bengaluru slum (12.26%) 13 . and much lower to the study conducted in Kollam (51.4%)[ 14 ] and in Mangalore Hospital (45.9%).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar findings revealed in other studies in India using similar tool for assessment. [3][4][5] In our study duration of diabetes was significantly related to better self-care practices, similarly Rajasekharan et al in Mangalore found better practices among participants with more duration of diabetes in few aspects, which might be due to accrued experience and exposure to self-care education measures also. 6 Likewise disease duration had significant association with practices in study by Tol et al 7 In present study self-care was significantly associated with age and education, and as predictable, were better among graduates and patients above 60 years of age.…”
Section: Discussionsupporting
confidence: 70%
“…further corroborates that diabetics in socioeconomically disadvantaged communities are at the risk of medication nonadherence. [ 2 ] The researchers utilized the medication subscale of the Summary of Diabetes self-care activities measure (SDSCA-MS) developed by Toobert et al . for assessing medication adherence.…”
mentioning
confidence: 99%